Penggunaan Media Sosial Baharu: Isu-Isu dan Panduan Perspektif Islam - Syed Abdul Rahman, Syed Mohammad Hilmi; Ramli, Mohd Anuar; Sa’ari, Che Zarrina; Norman, Azah Anir; Mamat, Mohd Anuar; Mohd Azhar, Muhammad Hazim (Jurnal Usuluddin, 2022)
Today’s technology advancements, which have sparked the creation of modern social media platforms, have also had an impact on society and everyday human life. This latest development, however, has sparked concerns about the potential for misuse. Various types of abuses have occurred in the absence of Islamic and spiritual instructions to communicate. Such as cyberbullying, unrestricted free expression, online harassment, and the distribution of false information. As a result, this report will explore concerns relating to new social media bullying as well as recommendations for dealing with it. To accomplish these goals, this qualitative research employs a full library approach, compiling and reviewing social media-related topics from journal papers, newspaper interviews, and websites. According to the study’s findings, there are a variety of problems or cases relating to the misuse of modern social media that have been identified, and essentially, social media users need to uphold Islamic morality while engaging on new social media in order for the digital righteousness environment to be achieved.